Associação entre atividade física no lazer, religião e fatores socioeconômicos em trabalhadores de uma universidade do nordeste brasileiro - SANTOS, Denilson de Menezes (2024)
Objective: Analyze the association between the level of physical activity and religion in university workers. Materials and methods: The target population of this study were the administrative and outsourced technicians of the Dom Delgado Campus of the Federal University of Maranhão. At the Dom Delgado campus. This study was submitted to the Ethics Committee for Research involving Human Beings of the Federal University of Maranhão (UFMA) with Certificate of Presentation of Ethical Appreciation number 64532322.3.0000.5087 and favorable opinion number 1,318,361, in accordance with the provisions of the Declaration of Helsinki and resolution no. 466/12 of the National Health Council. The data were obtained through the Physical Activity and Health Map – MAFIS, a questionnaire developed for the online environment with the aim of assessing lifestyle, in person and through WhatsApp groups in each sector of the campus, receiving the link to access the questionnaire and information about the research. Pearson's chi-square test was used to investigate possible associations between the main outcome variable and the secondary outcome variables. Finally, a binary logistic regression model was created with the level of physical activity as the dependent variable and all the variables of the secondary outcome as independent variables. In order to determine whether the independent variables impacted the model, the Wald test was adopted, with p-values lower than 0.05 indicating the presence of an impact. To assess the quality of the model, the Hosmer and Lemeshow test was calculated. Results: Individuals with no religion and higher incomes are more likely to be physically active, regardless of their preference for physical activity, time spent on hobbies, religion or volunteering, gender or age. Conclusion: It is concluded that physical activity in free time showed an inverse association with religion and a positive association with income among university workers in an academic community in northeastern Brazil, regardless of variables such as preferences for practicing physical